If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 5 = 3(5x + -4) + 10x Reorder the terms: 5 + 5x = 3(5x + -4) + 10x Reorder the terms: 5 + 5x = 3(-4 + 5x) + 10x 5 + 5x = (-4 * 3 + 5x * 3) + 10x 5 + 5x = (-12 + 15x) + 10x Combine like terms: 15x + 10x = 25x 5 + 5x = -12 + 25x Solving 5 + 5x = -12 + 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 5 + 5x + -25x = -12 + 25x + -25x Combine like terms: 5x + -25x = -20x 5 + -20x = -12 + 25x + -25x Combine like terms: 25x + -25x = 0 5 + -20x = -12 + 0 5 + -20x = -12 Add '-5' to each side of the equation. 5 + -5 + -20x = -12 + -5 Combine like terms: 5 + -5 = 0 0 + -20x = -12 + -5 -20x = -12 + -5 Combine like terms: -12 + -5 = -17 -20x = -17 Divide each side by '-20'. x = 0.85 Simplifying x = 0.85
| 12t-3t=36+5t | | 5k-7=12k+21 | | 1,875=1/3% | | 6x+3y=1fory | | -y+5=37 | | 5a=46 | | 2350/8225= | | 1,875=1/4% | | 38-7x=-12x | | 4x^2-5x+28=3x^2+x | | 2(-10+7x)=-20 | | -6+8m=122 | | 6x^2-24x=-16 | | 4C+2P=94 | | 85=28x+36 | | -3w-2z=-8 | | -6+8=122 | | 20=-4.9t^2+40t | | 12x+12-(x-1)=12 | | -(y+6)+2y-4=-19 | | 8+z=42 | | 6x+y+9=9x | | 6=-2x+6 | | .38x=34 | | 3(x+4)=-2(5x-8)+7x | | 4x+18=2(x+6) | | -2(4z-3)+9(z-6)=-32-8 | | 6x+7=(m) | | -20x-(-15x)=-165 | | 11-3(2x+4y)= | | 3x+2=10x-26 | | -8+14=-2(4v-7) |